Effect of Al3+ substitution on structural, morphological, magnetic, optical, and functional study of ZnFe2O4 nanoparticles - M. Sundararajan; Kholod Dahlous; M. Ramesh; R. S. Rimal Isaac; S. Yuvaraj; Jothi Ramalingam Rajabathar; Chandra Sekhar Dash; P. Aji Udhaya (AIP Advances)
ZnFe1−xAlxO4 (x = 0.0, 0.1, 0.3, and 0.5) samples were synthesized by the combustion method. The x-ray diffraction pattern confirms that the ferrite samples have a cubic inverse spinel structure, and Rietveld refinement adds more weight to this conclusion. Furthermore, the space group is Fd 3 ̄ m. Using Rietveld analysis, the oxygen location, lattice parameter, and cation distribution were found, proving that Al doped ZnFe2O4 ferrites were present in every sample. According to structural research, when the Al3+ concentration increases, the crystallite size decreases (15–29 nm) but the lattice parameter increases (8.399–8.418 Å). The FE-SEM images are agglomerated for all the ferrite samples. The estimated energy gap (1.83–2.05 eV) increases as the doping concentration is increased. The FT-IR spectrum revealed the formation of Al doped ZnFe2O4 nanoparticles, and vibrating sample magnetometry showed the ferromagnetic behavior.